Planting Materials Seed Systems of Finger Millet, Rice and Taro in Jumla, Kaski and Bara Districts of Nepal (Nepal Agriculture Research Journal, 2010)
Formal and informal seed supply systems of rice (Jumla, Bara and Kaski), finger millet and taro(Kaski) were studied in three ecosites of Nepal during 1999-2001 to understand the processes ofseed flow, seed production, seed selection and storage systems. A survey was conducted at 48 to96 households. Informal seed supply was the only system in Jumla and Kaski and formal systemexisted only in Bara. The main sources of seed were farmer's own saved seed (67-91%), seedfrom neighbors and relatives. Exchange of germplasm was the main basis of fulfillment fromother sources. All farmers obtained seed from their own village, while farmers introducedmaterials occasionally from outside village. Most of the farmers followed seed selection beforeor after crop harvest. Rice field selection and plant selection based on a fixed set of criteria wasthe common practice. Non lodged plants with more grain per panicle, bold grains, well-maturedand uniform plants, long panicle, true to type, good looking grains, free from diseases andinsects were the main rice seed selection criteria. All farmers from both sites stored rice seeds bylocal methods in the locally available containers. Mor and Mudkothi are the special strawcontainers to store rice seed in Bara. Dhara is a special mud structure used to store rice seeds inJumla. Finger millet seed supply system was mostly similar to that of rice seed system. Ninetyone percent farmers saved seed for their own use; however, many of them changed finger milletseeds lots or varieties regularly for their particular plot. Ears selection during harvest by setcriteria for seed purpose was the common practice. Farmers stored finger millet seed carefully insmall locally available containers and tried their best to maintain the quality of seed duringdifferent stage of seed production. Taro has diverse planting materials: cormels, corms witheyes, suckers and corm with small cormels. Taro planting materials management is totallyinformal and almost 89% farmers saved these materials for their use and replaced them mostlyafter 3 years. Farmers had fixed criteria of corms and cormels selection for planting purpose andfocus and more on disease free. Storage of planting materials was locally by using localmaterials and methods. Understanding of seed system in various crops helps to developconservation strategy.Key words: Seed flow; seed production; seed selection; seed storage; seed systemDOI: 10.3126/narj.v6i0.3343Nepal Agriculture Research Journal Vol.6 2005 pp.39-48